Cognition, Health Literacy, and Actual and Perceived Medicare Knowledge Among Inner-City Medicare Beneficiaries. (1st August 2016) - Sivakumar, Haran; Hanoch, Yaniv; Barnes, Andrew J.; Federman, Alex D.
Abstract : Poor Medicare knowledge is associated with worse health outcomes, especially in low-income patients. We examined the association of health literacy and cognition with actual and perceived Medicare knowledge in a sample of inner-city older adults. We conducted a cross-sectional analysis of data on 336 adults ages 65 years and older with Medicare coverage recruited from senior centers and low-income housing facilities in Manhattan, New York. Actual Medicare knowledge was determined by a summary score of 9 true/false questions about the Medicare program and perceived Medicare knowledge with a single item. Validated measures were used to assess health literacy and general cognition. Among respondents, 63.1% had high actual Medicare knowledge, and 36.0% believed that they knew what they needed to know about Medicare. Actual and perceived Medicare knowledge were poorly correlated ( r  = −.01, p  > .05). In multivariable models, low health literacy was significantly associated with actual Medicare knowledge (β = −8.30, SE  = 2.71, p  < .01) but not perceived Medicare knowledge (β = 0.37, SE  = 0.22, p  = .09). Individuals with low health literacy were more likely to perceive their Medicare knowledge as adequate when actual Medicare knowledge was low (adjusted odds ratio = 3.30, 95% confidence interval [1.20, 9.05], p  < .05). These results show that older adults with low health literacy are more likely to have poor understanding of the Medicare program and yet more likely to believe that their understanding of the program is adequate. This combination of factors may place them at increased risk for poor access to information about the Medicare program and diminish their ability to make fully informed choices.